2000
DOI: 10.1289/ehp.00108559
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic effects of alpha-endosulfan and beta-endosulfan on human HepG2 cells.

Abstract: alpha-Endosulfan and ss-endosulfan are isomers of endosulfan, a pesticide used worldwide. In this study, we examined the genotoxicity of [alpha]- and ss-endosulfan in vitro with a HepG2 cell line. We used sister chromatid exchanges (SCE), micronuclei (MN), and DNA strand breaks as detected by single-cell gel electrophoresis (SCG) assays as biomarkers to judge the genotoxicity of [alpha]- and ss-endosulfan at concentrations from 1 times 10(-12) M to 1 times 10(-3) M. After treating HepG2 cells for 48 hr with ss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…Higher values of tail moment and OTM of the T0 sample clearly suggest genotoxicity of the untreated sample. Previous studies have also reported genotoxicity of endosulfan in aquatic organisms (Sharma et al, 2007), white clovers (Liu et al, 2009), human HepG2 cells (Lu et al, 2000;Li et al, 2011) and human lymphocytes (Jamil et al, 2004;Bajpayee et al, 2006). It has been reported that even a sub lethal dose exposure of endosulfan causes oxidative stress environment inside the cell by altering the metabolic pathways and reduces the activities of various antioxidant enzymes like superoxide dismutase, glutathione peroxidise and glutathione-S-transferase leading to DNA damage (Ledirac et al, 2005;El-Shenawy, 2010).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Higher values of tail moment and OTM of the T0 sample clearly suggest genotoxicity of the untreated sample. Previous studies have also reported genotoxicity of endosulfan in aquatic organisms (Sharma et al, 2007), white clovers (Liu et al, 2009), human HepG2 cells (Lu et al, 2000;Li et al, 2011) and human lymphocytes (Jamil et al, 2004;Bajpayee et al, 2006). It has been reported that even a sub lethal dose exposure of endosulfan causes oxidative stress environment inside the cell by altering the metabolic pathways and reduces the activities of various antioxidant enzymes like superoxide dismutase, glutathione peroxidise and glutathione-S-transferase leading to DNA damage (Ledirac et al, 2005;El-Shenawy, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…The adverse effects of endosulfan have been shown through various aquatic (Siddique et al, 2003a,b) and mammalian cell line based bioassays (Li et al, 2011). It has been reported in endocrine disruption (US EPA, 2002), as being mutagenic (Bajpayee et al, 2006) as well as genotoxic (Lu et al, 2000) and neurotoxic (Paul and Balasubramaniam, 1997). Endosulfan is listed as a persistent organic pollutant (POP) and the global ban on its manufacture and use was negotiated under the Stockholm Convention.…”
Section: And the Us Environmental Protectionmentioning
confidence: 99%
“…In the trinitrotoluene study, the LC 50 was around 100 µg/mL, indicating that PCP is more toxic to HepG 2 cells as compared to TNT. Another study reported that isomers of endosulfan (alpha and ss) caused concentration-dependent genotoxic effects in HepG 2 cells [31]. Increased concentrations of alpha-and ss-endosulfan caused an increase in sister chromatid exchanges in HepG 2 cells upon 48 h of exposure, as well as DNA strand breaks within 1 h of exposure.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…These pesticides have been reported not only to cause serious diseases in humans but are detrimental to soil microflora (Megharaj, 2002). The major health effects due to pesticide are neuropathy headache, memory loss, bradycardia, jaundice, respiratory, depression, breathlessness and birth defects that occurs through food chain (Lu et al, 2000;Sinha et al, 1993). The use of these pesticides, especially DDT and HCH has therefore been either banned or restricted in several countries including India.…”
Section: Introductionmentioning
confidence: 99%